Histopathology of chronic spontaneous urticaria with occasional bruising lesions is not significantly different from urticaria with typical wheals. (15th March 2021) - Batista, Mariana; Calado, Rebeca; Gil, Francisco; Cardoso, José C.; Tellechea, Oscar; Gonçalo, Margarida
Abstract: Background: Chronic spontaneous urticaria (CSU) may occasionally exhibit long‐lasting lesions with bruising, usually considered a hallmark of urticarial vasculitis (UV). Histopathology of these chronic urticarial lesions has not been extensively studied. Methods: Skin biopsies from patients with anti‐H1 resistant CSU were evaluated for several parameters (edema, location, intensity, and cell composition of the inflammatory infiltrate, and abnormalities in the blood vessels). Results: We studied 45 patients (37 female/8 male, mean age 49.3 years) with CSU, 60% of whom with occasional bruising lesions and 3 patients with hypocomplementemic UV. Histopathology in CSU showed mainly perivascular and interstitial inflammatory infiltrate (91.1%), including eosinophils (80%), neutrophils (77.8%), and lymphocytes (71.1%), vasodilatation (88.9%), intravascular neutrophils (95.6%), dermal edema (51.1%), swelling of endothelial cells (51.1%), and minor and rare fibrinoid necrosis and karyorrhexis (6.7%). Significant karyorrhexis and frank fibrinoid necrosis were observed, respectively, in two and three cases of UV. In patients with occasional bruising, mast cells occurred in fewer cases whereas eosinophils were more frequent, but no statistically significant difference was found for other parameters. Conclusions: Histopathological findings were not significantly different between CSU with or without bruising lesions. Bruising may be associated with more severe forms of CSU with no histopathological signature, although UV cannot be completely excluded based on histopathology.